The Indonesian Blasphemy Law as Legal Forum for Renegotiating Indonesian Secularity - Muktiono (Human Rights in the Global South (HRGS), 2022)
If secularism is described merely as the decline of religious roles in public spheres or religious privatization, then there would be difficulties to put the secular term on Indonesian history. The principle of divinity “Ketuhanan Yang Maha Esa” as adopted on the “Pancasila” as state ideology has become basis for religionization and rejecting any utterance of secularism at law, State institution, or other public domain. On the other hand, Indonesia as a democratic State as well as the most populous Muslim country in the world has never put the notion of Islamic state or theocracy as its State model. Its modernity is developed under the Western idea of law supremacy or the rule of law to which a democratic political system is laid down. This situation seems to be paradoxical in the view of both religionist or modernist due to its inconsistency to their strict concept especially on Islamic state and secularism. Or, is Indonesia another example of how religion and modernity has its multiplicity based its own historical reflexivity without making clash between religion and secularism? This article is intended to seek kind of distinction on Indonesian secularity based on how its blasphemy law developed and functioned under the framework of open-ended negotiation. The first epoch assumed as the place of negotiation on Indonesian secularity was taken place on initial stage of State’s formation around transition era of independence in 1945. Then, there have been several renegotiations afterward through multiple and overlapping instruments of development such as politics, economy, law, and culture. The blasphemy law as one of such instruments will be used to read how the relevant actors of Indonesian history has constructed their own concept of state and religion included its interrelationship characters as the basis for social and structural differentiation or distinction. The expected outcome of the reading and its analysis is to reveal any evidence of Indonesian particularity on secularization which may be related to the concept of multiple secularities.